Analisis Perkembangan Moral Dan Spiritual Pada Santri Madrasah Diniyah Al-Mutma’innah Winong Jetis Ponorogo - Yuli Umro'atin (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2020)
Studying the development of humans and other creatures in general, we must distinguish two things, namely the process of maturation (maturation means the process of growth which involves perfecting bodily functions so as to cause changes in behavior regardless of the presence or absence of the learning process) and the process learning (learning, means changing or improving behavior through practice, experience and contact with the environment in humans is very important to learn through social contact so that people live in a society with a complex cultural structure). This research is located at Madrasah Diniyah Al-Mutma'innah Winong Jetis Ponorogo. This research uses a qualitative approach, which is a case study, which examines in depth all the events related to the discussion. The method used in gathering information in the field is the method of observation and in-depth interviews. Analysis of the data used is data reduction, data presentation and conclusions. From the results of research in the field, it is known that: 1) Moral development of madrasa diniyah al-Mutma'innah students includes: The majority of madrasa santri have behaved well even though not yet 100%, have characteristics or uniqueness of each in terms of moral / behavior, behave politely, respect to the teacher, behave well to the surrounding community, and peers even though it is not yet optimal and need better guidance, have a sense of responsibility towards himself, the teacher and fellow friends, and like to imitate everything they see, observe, and they hear. 2) The spiritual development of children / santri madrasah diniyah al-Mutma'innah is as follows: The students have begun to recognize their true identity as servants of Allah SWT, believe in the existence of God the Creator, Angels, Apostles, and the book of God, know their true identity as students study Islamic religion in madrasa, start practicing worship both in madrasa and in the community / residence, have an enthusiastic attitude and enthusiasm in learning the Koran including tartilnya, memorization and recitation, have a high enthusiasm in learning, creativity, adventure outside and others. 3) Factors that influence students' moral and spiritual development are internal and external factors.